2019
DOI: 10.1111/vco.12471
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor‐related apoptosis‐inducing ligand induces apoptosis in canine hemangiosarcoma cells in vitro

Abstract: Tumour necrosis factor‐related apoptosis‐inducing ligand (TRAIL) is an apoptosis‐inducing cytokine that shows potential therapeutic value for human neoplasms, and is effective in some canine tumours; however, its potential for killing canine hemangiosarcoma (HSA) cells is unknown. Thus, we evaluated the proapoptotic effect of TRAIL in nine canine HSA cell lines. Cells (JuA1, JuB2, JuB2‐1, JuB4, Re11, Re12, Re21, Ud2 and Ud6) were cultured with three recombinant human TRAILs (rhTRAILs): TRAIL‐TEC derived from E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Consistent downregulation of both TRAIL mRNA and protein levels, and the positive correlation between TRAIL and downstream molecules, FADD and caspase-3, may imply that TRAILinduced extrinsic apoptotic signalling is disrupted in canine mammary carcinoma, even though the exact contribution of this pathway to ultimate tumorigenesis is questionable. However, it might be speculated that endogenous TRAIL suppresses the tumour development or progression in canine tumours while sparing normal cells, from the evidence of direct apoptosis-inducing effect of TRAIL to various cancer cell lines including mammary tumour, osteosarcoma, lymphoma and hemangiosarcoma in previous studies 21,22,32,33 and from the loss of In addition, as a relationship between TRAIL and its downstream molecules was observed, it could be suggested that the canine extrinsic apoptotic pathway may be organized in a similar manner to that in humans, even though the exact cellular mechanism, including TRAIL receptors, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent downregulation of both TRAIL mRNA and protein levels, and the positive correlation between TRAIL and downstream molecules, FADD and caspase-3, may imply that TRAILinduced extrinsic apoptotic signalling is disrupted in canine mammary carcinoma, even though the exact contribution of this pathway to ultimate tumorigenesis is questionable. However, it might be speculated that endogenous TRAIL suppresses the tumour development or progression in canine tumours while sparing normal cells, from the evidence of direct apoptosis-inducing effect of TRAIL to various cancer cell lines including mammary tumour, osteosarcoma, lymphoma and hemangiosarcoma in previous studies 21,22,32,33 and from the loss of In addition, as a relationship between TRAIL and its downstream molecules was observed, it could be suggested that the canine extrinsic apoptotic pathway may be organized in a similar manner to that in humans, even though the exact cellular mechanism, including TRAIL receptors, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…231 TRAIL and its receptor belong to the p53-independent extrinsic pathway of apoptosis induction and can lead to apoptosis independently of p53, commonly inactivated in HSA. 231 Thus far, it has been established in HSA that caspase-3 and -8 are at least partially involved in TRAIL-induced apoptosis. 231 In terms of Bcl-2 overexpression, also reported in HSA, 232 the only direct activator of caspase-3 is caspase-8.…”
Section: Ligand Induced Apoptosismentioning
confidence: 99%
“…231 Thus far, it has been established in HSA that caspase-3 and -8 are at least partially involved in TRAIL-induced apoptosis. 231 In terms of Bcl-2 overexpression, also reported in HSA, 232 the only direct activator of caspase-3 is caspase-8. 233 The expression of antiapoptotic factors, such as Bcl-2 and survivin, may contribute to the TRAIL-resistance in HSA.…”
Section: Ligand Induced Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…To validate cross-reactivity of anti-human PRDX1 or 2 antibodies used in the present study to canine PRDX1 or 2 proteins by western blotting, HeLa which expressed PRDX1 and 2 [9,16] and Re 12 which was derived from canine HSA [27] were selected. SDS-PAGE and western blotting was performed according to previous report [8]. Briefly, protein lysates were prepared, and electrophoresed with SDS-PAGE and then transferred onto polyvinylidene difluoride membranes (Cytiva, Tokyo, Japan).…”
Section: Validation Of Anti-human Prdx1 and 2 Antibodies Against Cani...mentioning
confidence: 99%